Implementation of Population Administration Information System in Realizing Orderly Population Administration in Nias Regency - Laoli, Masriana; Telaumbanua, Eliagus (Amkop Management Accounting Review (AMAR), 2025)
This research is motivated by the importance of success regarding the implementation of the population administration information system in orderly Population Administration in Nias Regency. The method used is a qualitative method with a descriptive approach. In this research, the author uses informants who know and relate to the problem. The data collection technique used in this research is through two ways, including secondary data (books, scientific works, and documents/archives) and primary data (obtained from the field, both observations and interviews). From the results of the research it can be seen that the implementation of the Population Information System in realizing orderly administration has not been maximized, because there are still several obstacles and do not yet have a Regional Regulation specifically on Population in Nias Regency, so there is still a lot that needs to be addressed. Reviewed from 4 policy implementation models according to Edward III, namely communication, disposition / attitude, resources, and bureaucratic structure. In this study, researchers also gained a new understanding that in the implementation of good state service population administration, it would be better if the apparatus not only carried out population administration activities, but also needed to pay attention and care about the general needs of the community.